2017
DOI: 10.1017/s0267190517000071
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Models as Written Corrective Feedback in English as a Foreign Language (EFL)Writing

Abstract: The language learning potential of writing has been an underresearched topic in the English as a foreign language (EFL) context. The present study investigates what Basque-Spanish EFL teenage learners (n = 60) notice when writing a composition in response to visual stimuli in a three-stage writing task including output, comparison, and delayed revision. The present study also explores how this noticing and feedback processing affects their subsequent revisions. The findings revealed that participants noticed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
43
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 28 publications
11
43
2
Order By: Relevance
“…For example, Hanaoka (2007) showed that WCF was more likely to direct the attention of Japanese learners of English to lexical errors but not to other types of errors. Similar findings were observed in the study of García Mayo and Labandibar (2017) conducted with Spanish learners of English. In the study of Simard et al (2015), although learners could notice WCF triggered by lexical errors, they sometimes wrongly interpreted teachers' intention of correcting word choice errors as spelling errors.…”
Section: Effect Of Error Type On Written Corrective Feedbacksupporting
confidence: 89%
“…For example, Hanaoka (2007) showed that WCF was more likely to direct the attention of Japanese learners of English to lexical errors but not to other types of errors. Similar findings were observed in the study of García Mayo and Labandibar (2017) conducted with Spanish learners of English. In the study of Simard et al (2015), although learners could notice WCF triggered by lexical errors, they sometimes wrongly interpreted teachers' intention of correcting word choice errors as spelling errors.…”
Section: Effect Of Error Type On Written Corrective Feedbacksupporting
confidence: 89%
“…However, the direct CF group benefitted more from teacher"s written CF over time. These results go hand in hand with earlier works on the higher positive effect of direct CF when compared to indirect CF on written accuracy (Ellis et al, 2008;García Mayo and Labandibar, 2017;Sarvestani and Pishkar, 2015).…”
Section: Data Analysis and Discussion Of Resultssupporting
confidence: 66%
“…Thus, provided that CF on Primary Education L2 English students" writing skills is not a sufficient way by itself to improve their written accuracy, oral discussions on specific grammar structures, lexical topics or text coherence techniques should also be taken into account. The use of other CF techniques such as the use of model texts is also a very interesting topic for further analysis (Coyle et al, 2018;García Mayo and Labandibar, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations